2001
DOI: 10.1111/1467-9361.00130
|View full text |Cite
|
Sign up to set email alerts
|

Productivity Growth and its Components in Chinese Agriculture after Reforms

Abstract: This study uses nonparametric Malmquist procedures to investigate the temporal and spatial nature of productivity growth and its components in Chinese agriculture over the period 1980-1995. The results of this study indicate that total factor productivity grew at 2.4% annually with technical change augmenting the growth by 3.8% while efficiency change reduced productivity growth by 1.3%. For all provinces, 288 out of a total of 442 cases experienced productivity growth while the rest showed productivity regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 23 publications
3
24
0
Order By: Relevance
“…For example, Fan (1997) showed that agricultural productivity increased 3.9% per annum between 1985 and 1995. Wu et al (2001) found an increase of 3.6% between 1990 and 1995. Jin et al (2002) found that productivity of wheat increased by more than 20% between 1990.…”
Section: Related Literaturementioning
confidence: 92%
“…For example, Fan (1997) showed that agricultural productivity increased 3.9% per annum between 1985 and 1995. Wu et al (2001) found an increase of 3.6% between 1990 and 1995. Jin et al (2002) found that productivity of wheat increased by more than 20% between 1990.…”
Section: Related Literaturementioning
confidence: 92%
“…We use the level of aggregate output as weights in calculating the averages.15 We thank an anonymous referee for pointing out the importance of black markets for agricultural inputs and outputs.16 Wu et al (2001), using the Malmquist approach based on province level data, find the same rate of TFP growth for Chinese agriculture as a whole from 1990 to 1993.…”
mentioning
confidence: 96%
“…For China: Brummer et al (2006), Carter et al (2003), Chen and Ding (2007), Fan and Zhang (2002), Jin et al (2002), Kalirajan et al (1996), Liu and Wang (2005), Mao and Koo (2002), Mead (2003), Wang and Kalirajan (2002), Wen (1993), Wu et al (2001) and Zhang and Carter (1997). …”
mentioning
confidence: 99%